The Effect of Circular Training According to the Style of Stations (Physical - Skill) in Developing Some Physical Capabilities and Aiming by Jumping in Basketball for Youth - Rashad Tariq Yousef1 , Bahaa Dhyab Faisal2 , Hikmat Abdel Sattar Alwan3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The aim of the research is to identify the effect of circular training according to the stations’ method (physical- skill) In developing some physical abilities and shooting skills from basketball jumping, the researchcommunity included (28) players representing Al-Nasiriyah youth club basketball players (16-18 years old)for the season (2018-2019). (20) players were chosen from them representing a sample The research wasdivided into two groups randomly into two groups one What a pilot and another officer and by 10 players foreach group. . The researchers applied the circular training in a method (high intensity fatality) as it celebratesspecial exercises to develop the distinctive strength of speed for the arms, legs, back and abdomen, and theexplosive ability of the arms and legs, as well as the development of correction skill from jumping by (18)training units at a rate of (3) training units per week, concluded The two researchers in the experimentalgroup that applied circular training according to the style of stations (physical - skill) a marked superiorityover the control group in some physical abilities and the correction of jumping skill.